The Application of Asam Sunti as Feed Additives for Bacterial Infection Control of Edwardsiella tarda - Zulhan Efendi; Suhartono Suhartono; Firdus Firdus (The Faculty of Veterinary Medicine of Syiah Kuala University, 2023)
Cultivating catfish is one of the businesses that are of interest in Indonesia. The success of cultivation begins to be determined by the provision of seeds. Healthy seeds lead to a high survival rate, and unhealthy seeds due to disease will cause a high mortality rate, causing losses in the cultivation business. Bacterial infectious diseases Edwardsiella tarda can cause a low survival rate of catfish seeds, and even the death rate can reach 100%. This study aimed to evaluate and determine the best dosage of asam sunti in feed to control the pathogenic bacteria E. tarda infection in catfish. Asam sunti was given through feed with different treatment doses, with concentrate 0% (K), 0.5% (P1), 1% (P2), 2% (P3), and 4% (P4) for 14 days after being infected with pathogenic bacteria. The effect of giving asam sunti was measured by observing the survival of fish. The results showed that the administration of asam sunti could control the bacterial diseases of E. tarda bacteria sequentially control (K) is 0%, (P1) is 16.67%, (P2) 40%, (P3) 66.67%, and (P4) 90%. From these results, it can be concluded that the 4% asam sunti dose is the best dose for the survival of catfish seeds, with the survival rate for pathogenic bacteria E. tarda at 90%.